The Promise of Combining Radiation Therapy With Immunotherapy - Jagodinsky, Justin C.; Harari, Paul M.; Morris, Zachary S. (International journal of radiation oncology, biology, physics, 2020)
The development of immunotherapy in oncology builds upon many years of scientific investigation into the cellular mechanics underlying interactions between tumor cells and immune cell populations. The past decade has brought an accelerating pace to the clinical investigation of new immunotherapy agents, particularly in the setting of metastatic disease. The integration of immunotherapy into phase 3 clinical trial design has lagged in settings of advanced locoregional disease, where combination with radiation therapy may be critical. Yet, such may be the settings where immunotherapies have their greatest potential to affect patient survival and achieve curative outcomes. In this review, we discuss the interaction of radiation with the immune system and the potential to augment antitumor immunity through combined-modality approaches that integrate radiation and immunotherapies. The dynamics of cellular and tumor response to radiation offer unique opportunities for beneficial interplay with immunotherapy that may go unrecognized with conventional screening and monotherapy clinical testing of novel pharmaceutical agents. Using immune checkpoint blockade as a primary example, we discuss recent preclinical and clinical studies that illustrate the potential synergy of such therapies in combination with radiation, and we highlight the potential clinical value of such interactions. For various immunotherapy agents, their greatest clinical effect may rest in combination with radiation, and efforts to facilitate systematic investigation of this approach are highly warranted.